2017
DOI: 10.1016/j.jacc.2017.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation Versus Medical Rate Control in Atrial Fibrillation and Systolic Dysfunction

Abstract: AF is an underappreciated reversible cause of LVSD in this population despite adequate rate control. The restoration of sinus rhythm with CA results in significant improvements in ventricular function, particularly in the absence of ventricular fibrosis on CMR. This outcome challenges the current treatment paradigm that rate control is the appropriate strategy in patients with AF and LVSD. (Catheter Ablation Versus Medical Rate Control in Atrial Fibrillation and Systolic Dysfunction [CAMERA-MRI]; ACTRN12613000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
381
1
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 473 publications
(433 citation statements)
references
References 28 publications
10
381
1
19
Order By: Relevance
“…Anti‐Arrhythmic Drug Therapy for Atrial Fibrillation (http://clinicaltrials.gov identifier‐ NCT 00911508) and Early Treatment of Atrial Fibrillation for Stroke Prevention (http://clinicaltrials.gov identifier‐ NCT01288352) trials are in progress to address this question. Recently, however, in patients with heart failure reduced ejection fraction and AF, an ablation strategy compared to pharmacological rate/rhythm therapy has been shown to improve left ventricular systolic function as well as reduce heart failure hospitalisation and all‐cause mortality…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐Arrhythmic Drug Therapy for Atrial Fibrillation (http://clinicaltrials.gov identifier‐ NCT 00911508) and Early Treatment of Atrial Fibrillation for Stroke Prevention (http://clinicaltrials.gov identifier‐ NCT01288352) trials are in progress to address this question. Recently, however, in patients with heart failure reduced ejection fraction and AF, an ablation strategy compared to pharmacological rate/rhythm therapy has been shown to improve left ventricular systolic function as well as reduce heart failure hospitalisation and all‐cause mortality…”
Section: Discussionmentioning
confidence: 99%
“…The CAMERA-MRI multicenter trial (Catheter Ablation Versus Medical Rate Control in Atrial Fibrillation and Systolic Dysfunction) 15 showed that catheter ablation of AF was associated with an improvement in EF when compared with medical rate control (18% versus 4% improvement in EF) with a higher likelihood of normalization to ≥50% (58% versus 9%). The absence of LV late gadolinium enhancement by magnetic resonance imaging (MRI) predicted greater improvements in LV EF.…”
Section: Af Ablation In Heart Failurementioning
confidence: 99%
“…In another study of 1269 patients who underwent atrial flutter ablation, AIC was observed in 56% of the patients with concomitant LVSD 7. Furthermore, it was recently demonstrated that restoration of sinus rhythm with catheter ablation in patients with AF and LVSD results in significant improvements in LVEF compared with sole frequency control 6. The CASTLE‐AF study further revealed that catheter ablation for AF in patients with LVSD is associated with significant reduction of death from any cause and hospitalization for worsening heart failure 8.…”
Section: Discussionmentioning
confidence: 98%